Lead and Copper Concentration in Sediment and Blood Cockle (Anadara granosa) in the Coastal Waters of Panipahan, Rokan Hilir, Riau Province - Arnes, Arnes; Rifardi, Rifardi; Amin, Bintal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was conducted in March 2020 with the aim of evaluating the heavy metal content of Pb and Cu in sediment and blood cockle (Anadara granosa). The sediment and blood cockle samples were taken from Panipahan coastal waters, Panipahan Village and Teluk Pulai Village, Rokan Hilir Regency, Riau Province. The results of this study showed that the highest content of Pb and Cu in sediments was found in the surrounding area of residential areas (47.4570 µg / g and 104.1320 µg / g), while in blood cockle, the highest content was found around areas far from anthropogenic activity. The Pb content in the sediments did not show a significant effect on the Pb content in blood cockles, as well as the Cu. The results of the calculation of the MPI (Metal Pollution Index) value showed that Panipahan coastal waters are still classified as low pollution level